The Seroprevalence of transfusion transmissible hepatitis viruses in Kwara state Nigeria. - Osazee Ekundayo Izevbuwa (Hasanuddin University, 2022)
The burden of hepatocellular carcinoma as well as other health complications associated with infections due to Hepatis B and C Viruses are significant around the world. A number of research suggests that assumed healthy living individuals and potential blood donors are the major reservoirs of the Viruses in the community. During the course of this study, a total of 300 apparently healthy blood donors who presented to the blood group serology unit for blood donation across Ilorin, Kwara State, Nigeria, were screened to determine the Sero-prevalence of Transfusion Transmissible Hepatitis Viruses (Hepatitis B and C Viruses). Blood samples obtained from consented potential blood donors were collected and tested for Hepatitis B surface antigen (HBsAg) and Anti-HCV using immunochromatographic methods. The positive samples after the initial qualitative screening were subjected to Enzyme Linked Immunosorbent assay (ELISA) for confirmation of HBV and HCV Immunoglobulin G (IgG) following standard best practices. The results showed that 10% and 0.7% of the blood samples tested positive for HBV and HCV respectively. The male donors had more HBV infection 24 (8.0%) than the females 6 (2.0%). Donors with O Rhesus D positive blood type had more HBV infection 12 (4.0), while blood groups AB Negative, B Negative and O negative showed the least prevalence of 0 (0.0%). The age group of donors above 30 years of age had more HBV prevalence with 37.3% while the age group of 26 to 30 years showed the least prevalence of 28.7%. Data obtained from the piloted structured questionnaires designed to study the socio-demography of the participants showed that HBV was more prevalent among single blood donors, Civil servant/professional workers, and among blood donors that have successfully completed their tertiary education. The data from this research however, showed a negative correlation between the spread of the transfusion transmissible hepatitis viruses and the educational/ occupational standards of the test subjects who were included in this research. The highest rates of viremia were recorded among blood donors residing in urban areas however, the prevalence was not statistically different (p≥0.05).